Cervical cancer screening coverage in urban and rural areas in Southeast Sulawesi: its determinants - Saimin, Juminten; Wicaksono, Satrio; Ashaeryanto, . (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Cervical cancer is a woman’s health problem that is still widespread throughout the world, especially in developing countries such as Indonesia. The high incidence of cervical cancer is related with early detection program. Visual inspection of acetic acid (VIA) is used as an alternative screening method because it is easier, cheaper and its effectiveness is not much different from the Pap test. There are differences on coverage of VIA test in urban and rural areas. This study aimed to identify determinants of cervical cancer screening coverage in urban and rural areas. The study was a cross sectional study. Total of 372 women who did the VIA test in urban areas of Kendari and rural areas of South Konawe in January to June 2016 were included in this study. Coverage of cervical cancer screening was examined in relation to the level of education, knowledge, distance of health facilities and family support. The data was analyzed using Chi-square test with a significance value p < 0.05. The majority of respondents were the age groupof 31-40 years old, low parity, and first intercourse at ≥ 17 years old. There were significant difference of education level (p=0.000), knowledge (p=0.000) and distance of health facilitiesin urban and rural areas (p=0.000). There was no significant differences between family support in urban and rural areas (p=0.224). In conclusions, education level, knowledge, and distance of health facilities are determinants of cervical cancer screening coverage in urban and rural areas in Southeast Sulawesi.